Modelling as The Development Instrument of Commodity and Financial Networks in Regional Economy - Popkov, Valerian Vladimirovich; Berg, Dmitry Borisovich; Selezneva, Nadezhda Alekseyevna; Ulyanova, Y.A. (Economy of Regions, 2015)
The article is devoted to investigations of the relationship of commodity-production and financial network structures in the regional economy as dual conjugate systems. Material flows (raw materials, goods, etc.) are circulating in the commodity network according to the Leontyev, input-output model. Nonmaterial flows of property rights, money, etc. in the financial network are reflecting the movement of material objects. Network structure is considered to be a complex of closed and open circuits that are carrying out two fundamentally different problems: a locally closed circuits are meeting local demands by supplying of locally produced goods that is providing self-reproduction of the local economy; open (or transit) circuits are providing export-import flows. The generation mechanism of «internal» money in closed circuits of commodity-production network is presented. Obtained theoretical results are illustrated by calculations of closed and open circuit flows in the municipality economy model. The mathematical model represents the mutual payments of population and companies in matrix form. It is found that the volume of turnover in closed circuits is about 28.5 % of total municipality economy model turnover and can be assured by «internal» non-inflationary money. The remaining 71.5 % of total turnover are corresponding to the flows in open circuits of the network providing export and import activity. It is summarized that the priority of innovative economy projects should be given to domestic consumption rather than exports.